99mTc-DMSA (V) in Evaluation of Osteosarcoma: Comparative Studies with 18F-FDG PET/CT in Detection of Primary and Malignant Lesions. (7th May 2012) - Bandopadhyaya, G. P.; Gupta, Priyanka; Singh, Archana; Shukla, Jaya; Rastogi, S.; Kumar, Rakesh; Malhotra, Arun
Abstract : To evaluate the role of 99m Tc-DMSA (V) and [ 18 F]FDG PET-CT in management of patients with osteosarcoma, 22 patients were included in our study. All patients underwent both 99m Tc-DMSA (V) and whole-body [ 18 F]FDG PET-CT scans within an interval of 1 week. 555–740 MBq of 99m Tc-DMSA (V) was injected i.v. the whole-body planar, SPECT images of primary site and chest were performed after 3-4 hours. [ 18 F]FDG PET-CT images were obtained 60 minutes after i.v. injection of 370 MBq of F-18 FDG. Both FDG PET-CT (mean SUVmax = 7.1) and DMSA (V) scans showed abnormal uptake at primary site in all the 22 patients (100% sensitivity for both). Whole-body PET-CT detected metastasis in 11 pts (lung mets in 10 and lung + bone mets in 1 patient). Whole-body planar DMSA (V) and SPECT detected bone metastasis in one patient, lung mets in 7 patients and LN in 1 patient. HRCT of chest confirmed lung mets in 10 patients and inflammatory lesion in one patient. 7 patients positive for mets on DMSA (V) scan had higher uptake in lung lesions as compared to FDG uptake on PET-CT. Three patients who did not show any DMSA uptake had subcentimeter lung nodule. Resuts of both 99m Tc-DMSA (V) (whole-body planar and SPECT imaging) and [ 18 F]FDG PET-CT were comparable in evaluation of primary site lesions and metastatic lesions greater than 1 cm. Though 99m Tc-DMSA (V) had higher uptake in the lesions as compared to [ 18 F]FDG PET-CT, the only advantage [ 18 F]FDG PET-CT had was that it could also detect subcentimeter lesions.